The Expression of Intentionally Implied Meaning in Modern Armenian - Kesoyan, Miranush (Bulletin of Yerevan University B: Philology, 2024)
The implied meaning in linguistics has been examined from various perspectives, and according to different criteria, different types of implied meaning has been distinguished. In particular, according to the intention of the speaker or author, in the absence or presence of a certain intention, unintentionally and intentionally implied meanings are distinguished. In this article intentionally implied meaning is examined, in particular the circumstances and tendencies that can lead to the intentional introduction of implied meaning in the speech. In the case of intentionally implied meaning, the choice of the language units is considered by the author/speaker; he/she chooses linguistic units to best convey what he/she has to say, according to the situation and his/her purpose, after thinking thoroughly. The speaker/author can disguise even the simplest thought with a special intention by passing it off as a intentionally implied meaning.In Armenian linguistics, the impled meaning has been little studied in general, and this article is an attempt to some extent to fill in that gap in this field.
Keywords: implied meaning; intentionally implied meaning; unintentionally implied meaning; intention; ethics; courtesy; indirect acts of speech; background knowledge; maneuver; implied attitude